Effect of Organic and Inorganic Manure on Growth And Yield of Okra in Ramdhuni, Sunsari - Karki, Shristi; Sapkota, Bipesh; Kharal, Salon; Neupane, Suraj; Dahal, Anuja; Koirala, Soma; Baral, Samata (International Journal on Food, Agriculture and Natural Resources, 2025)
Farmers consider chemical fertilizer to be the only reliable source of plant nutrients, but its use decreases the physical, chemical, and biological properties of soil. Therefore, a field experiment was conducted at Jibika College of Agricultural Sciences, Ramdhuni, Sunsari, Nepal, from March 2023 to July 2023 to assess the effectiveness of different organic and inorganic manures on the growth and yield of okra. The experiment was carried out in an RCBD design with seven treatments (poultry manure, goat manure, FYM, vermicompost, pig manure, the recommended dose of fertilizers, and the control), which were replicated three times. The Arka Anamika variety of okra was used as a test crop. After analyzing the organic manure, the rate of manure application was fixed based on the nitrogen content. Data were collected on growth parameters such as days to first germination, days to first flowering, plant height, plant diameter, and number of leaves per plant. Similarly, yield parameters, including fruit length, fruit diameter, fruit weight, and yield, were measured. Analysis of variance was performed on the data via R-studio, and significant means were compared via Duncan's multiple range test. After analyzing the data, we found that most of the growth parameters, such as plant height, stem diameter, number of leaves, largest leaf length, and breadth, were prominent in poultry manure. Similarly, growth parameters for fruit weight and yield were significantly greater in poultry manure, but fruit length was greater with chemical fertilizer application. Based on the findings of the experiments, it was concluded that, compared with other types of fertilizers, poultry manure is the most appropriate fertilizer source for the optimum performance of okra, which is recommended for farmers.